Analysis of the learning process in higher education of subjects taught virtually during the COVID-19 pandemic - Gazca Herrera, Luis Alejandro; Culebro Castillo, Karina; Coria Hernández, Rosa Elena (IE Revista de Investigación Educativa de la REDIECH, 2022)
Face-to-face education is a learning process that facilitates the link between teachers and students, increases motivation and promotes understanding of content. In online education, students and teachers collaborate in virtual environments; the teacher needs to adapt the content of their educational subjects to elements of digital educational resources that are clear to the student. Online education is not a new model, however, with the arrival of the COVID-19 pandemic, its required implementation was without planning, affecting student learning. The purpose of this study was to carry out a descriptive and parametric analysis of the subjects that were taught under the virtual modality at the undergraduate level to determine if it favored the learning process. The research was exploratory and explanatory with a quantitative approach. In the sample proportion test results, the research hypothesis was accepted, in which more than 85% of the students consider the offered courses as acceptable, good or excellent, favoring their learning; however, the proportion of students who wish to take the courses under the virtual modality, preferring face-to-face education, is less than 60%.